A case of different gene mutations in primary and metastatic lesions after EGFR-TKI treatment of lung cancer. Issue 6 (December 2020) - Xie, Shaonan; Deng, Huiyan; Liu, Guangjie; Liu, Qingyi
Background: It remains controversial whether patients with EGFR -mutant lung adenocarcinoma should stop using epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) after progression during treatment. Case report: We report a 35-year-old man with poorly differentiated adenocarcinoma of the left upper lobe and an exon 19 deletion (Ex19Del) mutation found by large-panel next-generation sequencing. The patient underwent video-assisted thoracoscopic surgery 12 months after oral administration of icotinib 125 mg tid, and the left upper lobe and surrounding lymph nodes were removed. Postoperative pathology supported a diagnosis of left upper lobe adenocarcinoma and subcarinal (1/2), main pulmonary artery window (1/2), and left hilar (1/2) lymph node metastases. The EGFR mutations in the residual lesions had disappeared, and Ex19Del mutations were still visible in the mediastinal lymph node metastasis. Conclusion: Spatial heterogeneity of the resistance mechanism may explain why patients who continue to receive EGFR-TKIs in combination with local therapies (e.g., radiotherapy) for progressing lesions may benefit even after progression during EGFR-TKI therapy. The loss of the EGFR mutation allele as a putative resistance mechanism requires additional preclinical and clinical confirmation.